Compressive Strength Analysis and Water Absorption of Paving Blocks Made from Polypropylene Plastic Seeds - Fauzi, Muhammad Arman Fauzi; Mustakim; Andi Bustam Didi (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
The increasing interest of consumers in paving blocks because the construction of paving block pavements is environmentally friendly where paving blocks are very good at helping to conserve groundwater, faster implementation, easy installation and maintenance, have a variety of shapes that add aesthetic value, and the price is easily affordable. The purpose of this study was to determine the effect of adding Polypropylene plastic (PP) pellets on the compressive strength of paving blocks and to determine the effect of adding Polypropylene plastic (PP) pellets on the water absorption of paving blocks. This research method uses an experimental method carried out in the laboratory of structures and materials, Muhammadiyah University of Parepare from July to September 2024. The results of this study indicate that the sutittusi of polypropylene plastic pellets affects the compressive strength of paving blocks. The compressive strength values of paving blocks at 28 days of curing age are 35.583 Mpa, 34.500 Mpa, 33.833 Mpa, and 33.417 Mpa for each variation of 0%, 2%, 5%, and 7%. So by looking at the results obtained above, the higher the percentage of polypropylene plastic pellet substitution, the lower the compressive strength value. While the water absorption value of paving blocks shows that the substitution of polypropylene plastic pellets affects the water absorption of paving blocks. Variations of 0%, 2%, 5%, and 7% are respectively 4.4%, 4.6%, 4.8%, and 5.2%. So by looking at the results obtained above, the higher the percentage of polypropylene plastic pellet substitution, the higher the water absorption.